A study on stress-strain behaviour of granite and sandstone using closed-circuit servo-controlled testing machine - Abdullah, Rini Asnida (2006)
The objective of this study is to adopt a fundamental approach towards understanding the behaviour of granite and sandstone under uniaxial compression. The study is based on the complete stress-strain curve that represents the rock deformation under loading at a constant strain rate. Indeed, the complete stress-strain curve covers the behaviour of rock both at pre- and post-peak failure phases. To obtain the curve, the compression test need to be carried out using closed-circuit servo-controlled testing machine, or machine of high stiffness. In this study, a series of unaxial compressive tests on samples of granite and sandstone were undertaken using 3000 kN Tinius Olsen servo-controlled testing machine. Based on the complete stress-strain curves obtained, the deformation behaviour for both rock types are compared. Parameters being compared include peak strength, strain at failure and deformational behaviour at pre- and post-peak stages. Study on post failure behaviour of rock is particularly important in designing excavation, where rock materials may have been highly fractured or display certain degree of failure.